Models of Cooperation in the Field of Sports Within the Framework of the "One Belt, one Way" Project - Elena V. SIBIRSKAYA; Lyudmila V. OVESHNIKOVA; Olga M. PASYNKOVA; Lubov N. CHAIKOVSKAYA; Innara R. LYAPINA (Communications of International Proceedings, 2022)
The purpose of writing a scientific article is to consider the project "one belt, one road" as a new opportunity for the global development of sports in Russia and China. In the process of implementing the presented goal, it is necessary to: - consider the basics of the "one belt, one road" project; - to identify the key factors of the development of sports as an element of the global world; - to conduct a system of evaluation of physical education and introduction to sports in Russia and China; - analyze agreements and other acts in the field of sports and physical culture development; - formation of a priority model of cooperation-sports of Russia and China within the framework of the "one belt, one road" project.
Keywords: innovative initiative; one poya – one way; development; cooperation